Natural Products: A Potential Source of Malaria Transmission Blocking Drugs? - Phanankosi Moyo; Grace Mugumbate; Jacobus N. Eloff; Abraham I. Louw; Vinesh J. Maharaj; Lyn-Marié Birkholtz (MDPI AG, 2020)
The ability to block human-to-mosquito and mosquito-to-human transmission of Plasmodium parasites is fundamental to accomplish the ambitious goal of malaria elimination. The WHO currently recommends only primaquine as a transmission-blocking drug but its use is severely restricted by toxicity in some populations. New, safe and clinically effective transmission-blocking drugs therefore need to be discovered. While natural products have been extensively investigated for the development of chemotherapeutic antimalarial agents, their potential use as transmission-blocking drugs is comparatively poorly explored. Here, we provide a comprehensive summary of the activities of natural products (and their derivatives) of plant and microbial origins against sexual stages of Plasmodium parasites and the Anopheles mosquito vector. We identify the prevailing challenges and opportunities and suggest how these can be mitigated and/or exploited in an endeavor to expedite transmission-blocking drug discovery efforts from natural products.